Cinta dalam jarak: Bagaimana komitmen pada pasangan long distance relationship (LDR)? - Nurul Isnaini; Ade Tiara; Tomy Suganda (PSYCOMEDIA : Jurnal Psikologi, 2024)
Long Distance Relationship (LDR) have become a common phenomenon in Indonesia, where couples are separated by significant physical distance. Communication technologies such as social media, phone calls, and video calls are used to maintain closeness. LDRs pose various challenges, including difficulties in maintaining intimacy and trust, as well as facing issues such as emotional loneliness and lack of physical presence. This study explores the phenomenon of commitment in the context of LDR, focusing on aspects of satisfaction level, quality of alternatives, and investment size. The research method used is qualitative with a phenomenological approach, using interviews and observations as data collection techniques and data analysis using the qualitative data processing application Nvivo 12 plus. The results show that commitment in LDR is influenced by satisfaction in the relationship, support from family and friends, and investment of time and effort in maintaining communication and closeness. The findings provide a deeper understanding of commitment in LDRs among couples in Indonesia. The aspect that most determines a couple’s ability to commit to an LDR couple is the satisfaction level.